8-Methoxycapnolactone and stigmasterol From Micromelum minutum - Ratna Asmah Susidarti; Marwadi Rahmani; Abdul Manaf Ali; M. Aspollah Sukari; Hazar B.M. Ismail; Julius Kulip; Peter G. Waterman (Indonesian Journal of Pharmacy, 2007)
The coumarin, 8-methoxycapnolactone and stigmasterol were isolated from the leaves of Micromelum minutum (Rutaceae) which collected from Sepilok, Sabah, Malaysia and their structures were characterized by spectroscopic methods.Key words: Micromelum minutum; Coumarin; 8-Methoxycapnolactone, Stigmasterol